Integrative characterization of tissue-specific 3D genome organization and associated transcriptional regulation in pig liver and muscle - Weiwei Zhou; Yani Huang; Chenyu Li; Mei Ge; Mingfang Zhou; Huashui Ai; Zhiyan Zhang (Functional & Integrative Genomics, 2026)

IMEA-Net: An edge-sensitive network for cropland change detection in high-resolution remote sensing images - Xiaoli Yuan; Li Chen; Jiang Zhang; Guoxiong Zhou; Mingfang Wang; Liujun Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

RTCrownNet: A dual-channel deep learning framework for accurate rubber tree crown extraction from UAV LiDAR point clouds - Li Li; Xiangjun Wang; Guoxiong Zhou; Huaiqing Zhang; Yongfei Xue; Mingfang He; Genhua Liu; Hengrui Wang; Hao Li (Computers and Electronics in Agriculture, 2025)

Homeodomain leucine zipper protein controls the lobed leaf formation by modulating auxin distribution in watermelon - Yimei Zhou; Chuchu Chen; Shiqi Yi; Kejia Zhang; Xiaolong Lyu; Jinghua Yang; Zhongyuan Hu; Mingfang Zhang (Theoretical and Applied Genetics, 2025)

ESR1-dependent suppression of LCN2 transcription reverses autophagy-linked ferroptosis and enhances sorafenib sensitivity in hepatocellular carcinoma - Mingfang Xu; Tran Sy Trung; Zhiyong Zhu; Shijia Li; Shicheng Gong; Nuo Cheng; Peng Zhou; Shuai Wang (Journal of Physiology and Biochemistry, 2025)

LVF: A language and vision fusion framework for tomato diseases segmentation - Yang Hu; Jiale Zhu; Guoxiong Zhou; Mingfang He; Mingjie Lv; Junhui Wang; Aibin Chen; Jinsheng Deng; Yichu Jiang (Computers and Electronics in Agriculture, 2024)

The first detection of mpox virus DNA from wastewater in China - Jin Xu; Chao Liu; Qun Zhang; Haining Zhu; Feng Cui; Zhiqiang Zhao; Mingfang Song; Bo Zhou; Yunxiao Zhang; Peilong Hu; Lei Li; Qin Wang; et al. (Science of The Total Environment, 2024)

A large presence/absence variation in the promotor of the ClLOG gene determines trichome elongation in watermelon - Yuyuan Ma; Yu Wang; Zhiqin Zhou; Runqin Zhang; Yiru Xie; Yihan Zhang; Yongming Bo; Xiaolong Lyu; Jinghua Yang; Mingfang Zhang; Zhongyuan Hu (Theoretical and Applied Genetics, 2024)

Effects of exogenous riboflavin or cytochrome addition on the cathodic reduction of Cr(VI) in microbial fuel cell with Shewanella putrefaciens - Jing Ding; Yonglei Guo; Mingfang Tang; Sijia Zhou (Environmental Science and Pollution Research, 2024)

The joint associations of ambient air pollutants and weather factors with mortality: Evidence from a national time-stratified case-crossover study in China - Qijiong Zhu; Min Yu; Guoxia Bai; Chunliang Zhou; Ruilin Meng; Biao Huang; Weiwei Gong; Haoming Zhang; Ruying Hu; Zhulin Hou; Yize Xiao; Donghui Jin; et al. (Science of The Total Environment, 2024)

The comparison of mortality burden between exposure to dry-cold events and wet-cold events: A nationwide study in China - Muyun Li; Wen Fang; Ruilin Meng; Jianxiong Hu; Guanhao He; Zhulin Hou; Maigeng Zhou; Chunliang Zhou; Sui Zhu; Yize Xiao; Min Yu; Biao Huang; et al. (Science of The Total Environment, 2023)

A precise apple leaf diseases detection using BCTNet under unconstrained environments - Yukai Zhang; Guoxiong Zhou; Aibin Chen; Mingfang He; Johnny Li; Yahui Hu (Computers and Electronics in Agriculture, 2023)

Allelic variations of ClACO gene improve nitrogen uptake via ethylene-mediated root architecture in watermelon - Kejia Zhang; Wei Gao; Yimei Zhou; Haoshun Zhao; Yuelin Xia; Mengyi Zhang; Yongming Bo; Xiaolong Lyu; Zhongyuan Hu; Jinghua Yang; Mingfang Zhang (Theoretical and Applied Genetics, 2023)

Game-theoretic robotic offloading via multi-agent learning for agricultural applications in heterogeneous networks - Anqi Zhu; Zhiwen Zeng; Songtao Guo; Huimin Lu; Mingfang Ma; Zongtan Zhou (Computers and Electronics in Agriculture, 2023)

Natural polymer Nicandra physaloides (L.) Gaertn seed gum mediated assembly of hydroxyapatite assembly as versatile sponge for water pollution control - Xudong Wu; Yazhou Wang; Li Zhou; Chengkun Cai; Mingfang Hu; Xiaofang Yu; Rong He; Wenkun Zhu (Journal of Cleaner Production, 2023)

Molecularly imprinted polymers embedded with double perovskite quantum dots: A ratiometric fluorescence sensor for visible and fluorescent determination of Rhein - Rongkun Zhu; Zengcheng Du; Mingfang Zhu; Huanru Liang; Shumei Wang; Qing Zhou; Rui Li; Yulan Li; Chaoying Zeng; Wenhao Liu; Qiqing Chen (Chemical Engineering Journal, 2023)

Correction to: Dietary supplementation with synbiotics improves growth performance, antioxidant status, immune function, and intestinal barrier function in broilers subjected to cyclic heat stress - Mingfang Du; Yefei Cheng; Yueping Chen; Shiqi Wang; Haoran Zhao; Chao Wen; Yanmin Zhou (Environmental Science and Pollution Research, 2022)

Dietary supplementation with synbiotics improves growth performance, antioxidant status, immune function, and intestinal barrier function in broilers subjected to cyclic heat stress - Mingfang Du; Yefei Cheng; Yueping Chen; Shiqi Wang; Haoran Zhao; Chao Wen; Yanmin Zhou (Environmental Science and Pollution Research, 2022)

An allelic variant in the ACS7 gene promotes primary root growth in watermelon - Ahmed Mahmoud; Rui Qi; Haoshun Zhao; Haiyang Yang; Nanqiao Liao; Abid Ali; Guy Kateta Malangisha; Yuyuan Ma; Kejia Zhang; Yimei Zhou; Yuelin Xia; Xiaolong Lyu; et al. (Theoretical and Applied Genetics, 2022)

Protective effects of dietary synbiotic supplementation on meat quality and oxidative status in broilers under heat stress - Yueping Chen; Yefei Cheng; Mingfang Du; Yanmin Zhou (Environmental Science and Pollution Research, 2021)

Vegetation cover—another dominant factor in determining global water resources in forested regions - Xiaohua Wei; Qiang Li; Mingfang Zhang; Krysta Giles‐Hansen; Wenfei Liu; Houbao Fan; Yi Wang; Guoyi Zhou; Shilong Piao; Shirong Liu (Global Change Biology, 2018)
Forested catchments provide critically important water resources. Due to dramatic global forest change over the past decades, the importance of including forest or vegetation change in the assessment of water resources under climate change has been highly recognized by Intergovernmental Panel on Climate Change (IPCC); however, this importance has not yet been examined quantitatively across the globe. Here, we used four remote sensing‐based indices to represent changes in vegetation cover in forest‐dominated regions, and then applied them to widely used models: the Fuh model and the Choudhury‐Yang model to assess relative contributions of vegetation and climate change to annual runoff variations from 2000 to 2011 in forested landscape (forest coverage >30%) across the globe. Our simulations show that the global average variation in annual runoff due to change in vegetation cover is 30.7% ± 22.5% with the rest attributed to climate change. Large annual runoff variation in response to vegetation change is found in tropical and boreal forests due to greater forest losses. Our simulations also demonstrate both offsetting and additive effects of vegetation cover and climate in determining water resource change. We conclude that vegetation cover change must be included in any global models for assessing global water resource change under climate change in forest‐dominant areas.

Depression Status and Associated Factors in Chinese Occupational Truck Drivers - Shiqin Shen; Yong Li; Mingfang Zhou; Chan Zhang; Yajin Jiang; Yuanyi Kang (Cell Biochemistry and Biophysics, 2013)